Engraving of Margaret of France (19th Century) - William Henry Mote (Wikimedia Commons, 1851)
Notice iconographique issue de Wikimedia Commons. Titre: Engraving of Margaret of France (19th Century). 19th Century Engraving of Margaret of France, Second wife of King Edward I
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie